Evaluation of the prognostic value of lateral MAPSE in patients with suspected coronary artery disease - Chengxi Yan; Ying Chang; FangWu; Minglei Yang; Shuangfeng Dai; Jiannan Zhang; Yuelang Zhang (International Journal of Cardiology: Heart & Vasculature)
Objectives: To evaluate the prognostic value of lateral mitral annular plane systolic excursion (MAPSE) in the prediction of major adverse cardiology events (MACE) in patients with suspected coronary artery disease (CAD). Methods: 233 consecutive patients were enrolled with suspected CAD from October 2012 to September 2013 and performed contrast-enhanced cardiac magnetic resonance (CMR) and two-dimensional echocardiogram studies no later than 72 h after admission. CMR imaging protocol included 4-chamber cine(cine-CMR), cardiovascular magnetic resonance angiography (CMRA) and late gadolinium enhancement (LGE). The primary endpoint is the time of first occurrence of a MACE The independent association between lateral MAPSE and MACE was evaluated by Kaplan-Meier analysis and multivariable Cox regression analysis. C statistic and net reclassification improvement (NRI) were used to evaluate the prognostic value of lateral MAPSE in MACE. Results: Forty-five MACE occurred during an average follow-up of 9.2 years. Patients with lateral MAPSE＜9.885 mm experienced a significantly higher incidence of MACE than patients with lateral MAPSE ≥ 9.885 mm (P＜0.001). After adjustment for established univariate predictors (age, diabetes, hypertension, hypercholesterolemia, transmural myocardial infarction), lateral MAPSE remained a significant independent predictor of MACE (HR = 1.373; P = 0.020). The incorporation of lateral MAPSE into the risk model resulted in significant improvement in C statistic (increasing from 0.668 to 0.844; P = 0.005). NRI improvement was 0.33 (P＜0.001). Conclusions: lateral MAPSE derived from cine-CMR is an independent predictor of MACE, and improve risk reclassification beyond traditional clinical and CMR risk factors in patients with suspected coronary disease.